PENGARUH METODE MIND MAPPING BERBASIS KATA-KATA MUTIARA TERHADAP KETERAMPILAN MEMBACA PEMAHAMAN DAN MENULIS NARASI SISWA SD - Muftianti, Agni (Universitas Pendidikan Indonesia, 2017)
This research is motivated by the problem of low ability to write narrative students, marked by the students less seriously and less have a strong will in writing narrative. This research is intended to know the effect of Mind Mapping method oriented pearl words to the skills of reading comprehension and writing narrative essay. In this research, used quasi experimental research design (nonequivalent group pretest-postest) using two groups that is experiment group and control group. The result of learning through Mind Mapping method with pearl oriented orientation toward reading comprehension skill and narrative writing skill showed better result, marked by the increase of mean value of experimental class after 91 test, while the mean value of control class after test is 81, 25. Then the average value of the post-test experiment class narrative is 81, while the average grade of the post-test control class is 71.5. Keywords: mind mapping, pearl words, reading comprehension, and narrative writing.